A qualitative exploration of barriers and enablers to providing autonomous independent pharmacist prescribing for common clinical conditions in community pharmacy - Lorna Brown; Rachel Bruce; Pamela Macintyre (International Journal of Pharmacy Practice, 2026)
Abstract Introduction In 2020, a national Pharmacy First Plus (PF+) service was introduced in Scotland to enhance healthcare access by enabling community pharmacists with an independent prescribing qualification to diagnose, manage and autonomously prescribe for a wider range of common clinical conditions. Data demonstrated service delivery is variable. Objectives This study aimed to explore the barriers and enablers to delivering PF+ by community pharmacies within National Health Service Greater Glasgow & Clyde (NHSGGC), the largest health board in Scotland. Method Between July and December 2023, 12 one-to-one semi-structured interviews with NHSGGC community pharmacist prescribers offering the PF+ service were conducted face to face or virtually. Audio recordings of the interviews were transcribed verbatim and underwent thematic analysis using normalization process theory. Key findings Analysis generated three overarching themes of individual, organizational and contractual factors. Subthemes were pharmacy logistics, clinical skills and training, staffing/skill mix, competing priorities, time challenges and external stakeholder relationships. Many of these were interdependent and had the potential to be a barrier or an enabler to PF+ provision, depending on context. Conclusion The barriers and enablers to community pharmacists working as autonomous prescribing pharmacists and delivering a standardized service are multifaceted. With growing opportunities to expand the PF+ service, it is important to address and influence the barriers that currently exist.